An Up-to-Date Joint Labor Supply and Child Care Choice Model - Thor O. Thoresen; Trine Engh Vattø (Center for Economic Studies and ifo Institute (CESifo), 2017)
Norwegian parents of preschool children make their care choices from a completely different choice set compared to what their predecessor did, say, two decades ago. Now, there is essentially only one type of nonparental care, center-based care, and at the parental side fathers take a more pivotal role in the early childhood care. In the present paper we develop a joint labor supply and child care choice model that accounts for these new characteristics of the family choice set – only one nonparental care option and both mothers and fathers contributing to the production of nonparental care. Even though Norway may be seen as a frontrunner in terms of both publicly subsidized care and gender equality, we believe that the model points to current and future modeling directions for several other economies too. The model is estimated on data on working hours and families' use of child care. We find that parents are not responsive to the price on center-based care, but respond more strongly to changes in wages. The average wage elasticity for mothers is in the range 0.25–0.30.
Keywords: J13; J22; C25; 330; family policy; child care; structural labor supply model